2022
DOI: 10.2147/nss.s378612
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Circadian Typology and Dry Eye Symptoms in Chinese College Students

Abstract: Purpose To explore the relationship between symptomatic dry eye and circadian typology in college students. Methods This study included 269 students from 3 Chinese universities. All participants completed the ocular surface disease index (OSDI) questionnaire, the morningness-eveningness questionnaire (MEQ), and the Pittsburgh sleep quality index (PSQI) questionnaire. Participants were grouped into 3 types by the reduced MEQ (rMEQ) score:E-Type, N-Type, and M-Type. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This study revealed that 39.30% of the participants experienced poor sleep quality as determined by the PSQI scale with a critical (40), and a study conducted in Beijing in 2021 identified a prevalence of 53.2% (41). Meanwhile, a survey conducted in Changsha reported that only 9.8% of university students suffer from sleep disorders (42), suggesting a substantial variation.…”
Section: Discussionmentioning
confidence: 75%
“…This study revealed that 39.30% of the participants experienced poor sleep quality as determined by the PSQI scale with a critical (40), and a study conducted in Beijing in 2021 identified a prevalence of 53.2% (41). Meanwhile, a survey conducted in Changsha reported that only 9.8% of university students suffer from sleep disorders (42), suggesting a substantial variation.…”
Section: Discussionmentioning
confidence: 75%